A Review: Biochemical Role of House Fly in the Transmission of Medically Important Parasites - Joel, Emmanuel Askebnde; Alooma, Emmanuel; Wilson, Ubur Terzulum; Umaru, Isaac John; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel (Kwaghe International Journal of Sciences and Technology, 2024)
House flies (Musca domestica) can be found everywhere in the world except Antarctica, especially in regions with dense populations, hot weather, and inadequate hygiene. They are insects of small to medium size, featuring a unique gray body and big compound eyes that are colored red. House flies experience full metamorphosis, which includes four separate life phases: egg, larva (maggot), pupa, and adult. House flies are seen as important pests for public health because they can carry various pathogens, such as bacteria, viruses, protozoa, and parasites. Because of their close connection to human actions, capability to travel far distances, and inclination to breed in decaying organic material, they are highly effective carriers for transmitting different illnesses. House flies have been linked to the spread of more than 100 different disease-causing microorganisms, leading to illnesses like gastroenteritis, dysentery, and cholera. Apart from bacterial pathogens, house flies have also been discovered to play a role in spreading different viruses and medically significant parasites. This review describes the physical characteristics and behavior of the house fly, highlighting its unique attributes like compound eyes, antennae, thorax, abdomen, and wings. The stages of development of a house fly, from egg to larva, pupa, and adult. It also offers distinct ways in which house flies can spread medically significant parasites, emphasizing the public health impact of this occurrence, especially in regions with inadequate sanitation and restricted healthcare access. It is essential to comprehend the role of house flies in transmitting these parasites in order to create successful control methods and enhance public health results.